Differential geographic patterns in song components of male Albert's lyrebirds. Issue 6 (14th February 2021) - Backhouse, Fiona; Dalziell, Anastasia H.; Magrath, Robert D.; Rice, Aaron N.; Crisologo, Taylor L.; Welbergen, Justin A.
Abstract: Geographic variation in bird song has received much attention in evolutionary studies, yet few consider components within songs that may be subject to different constraints and follow different evolutionary trajectories. Here, we quantify patterns of geographic variation in the socially transmitted "whistle" song of Albert's lyrebirds ( Menura alberti ), an oscine passerine renowned for its remarkable vocal abilities. Albert's lyrebirds are confined to narrow stretches of suitable habitat in Australia, allowing us to map likely paths of cultural transmission using a species distribution model and least cost paths. We use quantitative methods to divide the songs into three components present in all study populations: the introductory elements, the song body, and the final element. We compare geographic separation between populations with variation in these components as well as the full song. All populations were distinguishable by song, and songs varied according to the geographic distance between populations. However, within songs, only the introductory elements and song body could be used to distinguish among populations. The song body and final element changed with distance, but the introductory elements varied independently of geographic separation. These differing geographic patterns of within‐song variation are unexpected, given that the whistle song components are always produced in the same sequence and may be perceived as a temporally discrete unit. Knowledge of such spatial patterns of within‐song variation enables further work to determine possible selective pressures and constraints acting on each song component and provides spatially explicit targets for preserving cultural diversity. As such, our study highlights the importance for science and conservation of investigating spatial patterns within seemingly discrete behavioral traits at multiple levels of organization. Abstract : Male Albert's lyrebirds show geographic variation in their species‐specific whistle song, with acoustic differences between populations increasing with geographic distance. However, three discrete components within the song, the introduction, the body, and the final element, show contrasting patterns of spatial variation. This suggests that the same evolutionary drivers are not acting on each song component, demonstrating the importance of investigating spatial patterns in bird song at multiple levels of organization.